The life and work of St Paul - Farrar, Frederick William, 1831-1903 (London, UK Cassell and co, 1908)
Includes bibliographical references
First published 1879. A number of pages have not been cut at production. Inscription inside front cover : To my sunshine Lad from sister, June 15th, 1916. Inscription on title page : N.J. Parker from Alice Stirling, 1910.
Keywords: Paul, the Apostle, Saint -- Biography